Pemanfaatan energi terbarukan dalam upaya swasembada listrik di kawasan wisata edukasi pedesaan - Lanny Agustine; Albert Gunadhi; Diana L. Antonia; Widya A. Weliamto; Peter R. Angka; Rasional Sitepu; Hartono Pranjoto; Andrew Joewono; Yuliati Yuliati; Andrew F. Miyata (Jurnal Inovasi Hasil Pengabdian Masyarakat (JIPEMAS), 2021)
Cottok Innovation Park (CIP) is a tourist area that develops technology-based educational tourism. CIP is located on a broad hill. This area was in a barren state when the first service activities were carried out at the beginning of development in 2017. The PLN electricity network is also not yet available because it is far from residential areas. Solar-based technology has been applied and developed sustainably at CIP as an effort to be self-sufficient in electrical energy to provide water and lighting. Water is obtained by a solar pump from a groundwater source at a depth of 40 m. Currently, CIP has grown rapidly and provides night tours. The latest community service activities results are off-grid PLTS-based road signs and the CIP icon lamp to support night tourism. A further effect of this sustainable community service activity is the motivation and confidence of village youth to be involved in village development programs as tourist areas and children's education. It has also impacted the decline in the number of poor people in the village of Curah Cottok.